Single‐sided NMR to estimate morphological parameters of the trabecular bone structure. Issue 6 (22nd December 2020) - Barbieri, Marco; Fantazzini, Paola; Bortolotti, Villiam; Baruffaldi, Fabio; Festa, Anna; Manners, David N.; Testa, Claudia; Brizi, Leonardo
Abstract : Purpose: Single‐sided 1 H‐NMR is proposed for the estimation of morphological parameters of trabecular bone, and potentially the detection of pathophysiological alterations of bone structure. In this study, a new methodology was used to estimate such parameters without using an external reference signal, and to study intratrabecular and intertrabecular porosities, with a view to eventually scanning patients. Methods: Animal trabecular bone samples were analyzed by a single‐sided device. The Carr‐Purcell‐Meiboom‐Gill sequence of 1 H nuclei of fluids, including marrow, confined inside the bone, was analyzed by quasi‐continuous T2 distributions and separated into two 1 H pools: short and long T2 components. The NMR parameters were estimated using models of trabecular bone structure, and compared with the corresponding micro‐CT. Results: Without any further assumptions, the internal reference parameter (short T2 signal intensity fraction) enabled prediction of the micro‐CT parameters BV/TV (volume of the trabeculae/total sample volume) and BS/TV (external surface of the trabeculae/total sample volume) with linear correlation coefficient >0.80. The assignment of the two pools to intratrabecular and intertrabecular components yielded an estimate of average intratrabecular porosity (33 ± 5)%. Using the proposed models, the NMR‐estimated BV/TV and BS/TV were found to be linearly related to the corresponding micro‐CT values with high correlation (>0.90 for BV/TV; >0.80 for BS/TV) and agreement coefficients. Conclusion: Low‐field, low‐cost portable devices that rely on intrinsic magnetic field gradients and do not use ionizing radiation are viable tools for in vitro preclinical studies of pathophysiological structural alterations of trabecular bone.